2021
DOI: 10.3390/ma14133653
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Nanosilica Sol on the Hydration Process of Different Kinds of Cement and Mortar Properties

Abstract: Compared with nanosilica collected in a gaseous state, nanosilica sol has great economic value and application significance for improving the performance of concrete and mortar. In this study, the influence of nanosilica sol on the hydration process of different kinds of cement is studied by means of hydration heat analysis,X-ray diffraction analysis(XRD)and other methods, and the properties of mortar such as setting time, mechanical properties and porosity are also studied to characterize the influence of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…These materials can be acquired from industrial wastes, including fly ash (FA) [ 45 ], silica fume (SF) or microsilica (MS) [ 46 ], metakaolin (MK) [ 47 ], slag [ 48 ], nanosilica (NS), and even an agricultural waste, such as sugarcane bagasse ash [ 49 ]. Researchers have utilized various types of SCMs to improve the characteristics of cement-based structures [ 50 ]. Pozzolans can greatly improve the performance of cementitious materials in terms of their resistance to the chemical attack, durability, and strength [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…These materials can be acquired from industrial wastes, including fly ash (FA) [ 45 ], silica fume (SF) or microsilica (MS) [ 46 ], metakaolin (MK) [ 47 ], slag [ 48 ], nanosilica (NS), and even an agricultural waste, such as sugarcane bagasse ash [ 49 ]. Researchers have utilized various types of SCMs to improve the characteristics of cement-based structures [ 50 ]. Pozzolans can greatly improve the performance of cementitious materials in terms of their resistance to the chemical attack, durability, and strength [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials (nano SiO2, nano Al2O3, nano Fe2O3, etc.) have special nano size effect and pozzolanic activity, and are often used to improve the mechanical properties and microstructure of cement-based materials [4][5][6][7][8]. Xie studied the influence of nano Al2O3 on the early rheology, middle hydration and late mechanical properties of portland cement paste; the results showed that the addition of nano Al2O3 increased the plastic viscosity and the maximum increase of strength was more than 110% [9].…”
Section: Introductionmentioning
confidence: 99%
“…The most effective dosages of microsilica vary from 5 to 20%, depending on the raw materials used and the types of concrete. At the same time, the increase in strength characteristics varies from insignificant, when only microsilica is added, to quite impressive (30–80%), when other additives are used along with microsilica, in particular, flask and diatomite [ 27 ], fly ash [ 19 ], carbon nanotubes [ 26 ], nanosilica, and nanosilica sol [ 19 , 41 , 43 , 44 ]. Microsilica densifies and strengthens the structure, increasing its uniformity and stabilizing the cement hydration process [ 19 , 27 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nano-modification of concrete with nanosilica [ 12 , 13 , 18 , 19 , 23 , 24 , 25 , 35 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] has already shown efficiency in improving the properties of concrete, but still requires a solution for many issues. The main problem associated with the introduction of nanoparticles into cement-based materials is how to evenly distribute them in the matrix [ 23 ].…”
Section: Introductionmentioning
confidence: 99%